Determinants of Profitability in Nepalese Commercial Banks - Devkota, Aakriti; Khatri, Anuka; Mahato, Astika; Regmi, Bina; Khatri, Dipak Kumar; Pradhan, Radhe Shyam (Nepalese Journal of Business, 2025)
This study examines the factors affecting profitability of Nepalese commercial banks. Return on assets and return on equity are selected as the dependent variables. The selected independent variables are firm size, capital adequacy ratio, total debt to total equity, total equity to total assets, total debt to total assets, non- performing loan. The study is based on secondary data of 10 commercial banks with 100 observations for the study period from 2013/14 to 2022/23. The data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of factors determining the profitability of Nepalese commercial banks. The study showed that firm size has a positive impact on return on assets and return on equity. It indicates that larger the firm size, higher would be the return on assets and return on equity. Similarly, capital adequacy ratio has a positive impact on return on assets and return on equity. It indicates that higher the capital adequacy ratio, higher would be return on assets and return on equity. Likewise, total debt to total equity ratio has a negative effect on return on assets and return on equity. It indicates that higher the total debt to total equity ratio, lower would be the return on assets. In addition, total equity to total assets ratio has a negative effect on return on assets. It indicates that increase in total equity to total assets ratio leads to decrease in return on assets. Moreover, total debt to total assets ratio has a negative effect on return on assets. It means that increase in total debt to total assets ratio leads to decrease in return on assets. Furthermore, non-performing loans has a negative effect on return on assets and return on equity. It indicates that higher the non-performing loans, lower would be the return on assets and return on equity.